Registros notables de mamíferos para Campeche, México/Noteworthy records of mammals to Campeche, Mexico - Guzmán-Soriano, Daniela; Vargas-Contreras, Jorge A.; Cú-Vizcarra, José D.; Escalona Segura, Griselda; Retana Guiascón, Óscar G.; González Christen, Alvar; Benítez Torres, Jorge A.; Arroyo-Cabrales, Joaquín; Puc Cabrera, José C.; Victoria Chán, Eloy (Instituto de Ecología, A.C., 2013)
Se reportan ocho nuevos registros de mamíferos para Campeche, México, de los cuales siete son del orden Chiroptera y uno del orden Carnivora. A su vez, se confirma la presencia de Artibeus watsoni, Cynomops mexicanus (Chiroptera) y Lontra longicaudis (Carnivora) en el Estado, con lo cual la riqueza de especies de murciélagos se incrementa de 48 a 55 y de carnívoros de 16 a 17. We collected eight new records of mammal species from Campeche, México, including seven bats (Order Chiroptera) and one carnivore (Order Carnivora). We also confirmed the presence in the state of Artibeus watsoni, Cynomops mexicanus (Chiroptera) and Lontra longicaudis (Carnivora). Hence, for Campeche bat species richness increased from 48 to 55 and carnivores 16 to 17.